Propagation of Blue Honeysuckles (Lonicera caerulea L.) in In Vitro Culture - Krupa-Małkiewicz Marcelina; Ochmian Ireneusz (Journal of Basic & Applied Sciences, 2014)
The aim of this study was to develop micropropagation protocol for Lonicera caerulea L. Clone 44, Clone 46 and Br?zowa, three important invasive woody horticultural plants. Actively growing shoots from the shrubs grown in the field were used for initiation of culture. Shoots were surface sterilized with ethanol, then with sodium hypochlorite and mercury sulfate. MS medium supplemented with cytokinin BAP at concentrations of 1.0 - 4.0 mg·dm-3 had no statistically significant effect on the shoot initiation of selected blue honeysuckle genotypes. Multiplication rate varied depending on the genotype and plant growth regulator concentrations. The highest number of microshoots produced per explant of Clone 44 and Clone 46 was obtained at using 2.0 mg·dm-3 BAP, while of cultivar Br?zowa – 1.0 mg·dm-3 BAP. Shoots were rooted in vitro in the presence of IBA and IAA. Microshoots have rooted differently depending on the treatment and genotype. In the case of Clone 4458% rooting was achieved at 2.5 mg·dm-3 IBA and MS basal nutrient medium treatment.